onder één noemer zetten

$
\eqalign{
  & f(x) = x^2 \sqrt {1 - x^2 }   \cr
  & f'(x) = 2x\sqrt {1 - x^2 }  + x^2  \cdot {1 \over {2\sqrt {1 - x^2 } }} \cdot  - 2x  \cr
  & f'(x) = 2x\sqrt {1 - x^2 }  - {{x^3 } \over {\sqrt {1 - x^2 } }}  \cr
  & f'(x) = 2x\sqrt {1 - x^2 }  \cdot {{\sqrt {1 - x^2 } } \over {\sqrt {1 - x^2 } }} - {{x^3 } \over {\sqrt {1 - x^2 } }}  \cr
  & f'(x) = {{2x\left( {1 - x^2 } \right)} \over {\sqrt {1 - x^2 } }} - {{x^3 } \over {\sqrt {1 - x^2 } }}  \cr
  & f'(x) = {{2x - 2x^3  - x^3 } \over {\sqrt {1 - x^2 } }}  \cr
  & f'(x) = {{ - 3x^3  + 2x} \over {\sqrt {1 - x^2 } }} \cr}
$

©2004-2020 W.v.Ravenstein